Measurement of internet financial reporting with Moderate Regression Analysis - Martina Khusnul Umami; Imanda Firmantyas Putri Pertiwi (Indonesian Journal of Islamic Economics Research, 2022)
Effect of Return on Equity, Quick Ratio, Debt to Equity Ratio on Internet Financial Reporting with managerial ownership as a moderating variable in the JII70. This research is motivated by the increase or the number of qualities of internet use in various ways, one of which is the economic field. Companies must report their operational activities by keeping up with the times so that investors can see company performance more quickly and efficiently. This study aimed to determine the effect of Return on Equity, Quick Ratio, and Debt to Equity Ratio on Internet Financial Reporting with managerial ownership as a moderating variable for the study on JII70 for the 2018-2021 period. The results of this study indicate that Return on Equity does not affect Internet Financial Reporting. In contrast, the quick and debt-to-equity ratios affect Internet Financial Reporting. Return on Equity, Quick Ratio, and Debt to Equity Ratio moderated by managerial ownership cannot affect Internet Financial Reporting.